Competing Roles of Two Kinds of Ligand during Nonclassical Crystallization of Pillared‐Layer Metal‐Organic Frameworks Elucidated Using Microfluidic Systems. Issue 41 (9th July 2020) - Tanaka, Yoko; Kitamura, Yu; Kawano, Ryuji; Shoji, Kan; Hiratani, Moe; Honma, Tetsuo; Takaya, Hikaru; Yoshikawa, Hirofumi; Tsuruoka, Takaaki; Tanaka, Daisuke
Abstract: To diversify metal‐organic frameworks (MOFs), multi‐component MOFs constructed from more than two kinds of bridging ligand have been actively investigated due to the high degree of design freedom afforded by the combination of multiple ligands. Predicting the synthesis conditions for such MOFs requires an understanding of the crystallization mechanism, which has so far remained elusive. In this context, microflow systems are efficient tools for capturing non‐equilibrium states as they facilitate precise and efficient mixing with reaction times that correspond to the distance from the mixing point, thus enabling reliable control of non‐equilibrium crystallization processes. Herein, we prepared coordination polymers with pillared‐layer structures and observed the intermediates in the syntheses with an in‐situ measurement system that combines microflow reaction with UV/Vis and X‐ray absorption fine‐structure spectroscopies, thereby enabling their rapid nucleation to be monitored. Based on the results, a three‐step nonclassical nucleation mechanism involving two kinds of intermediate is proposed. Abstract : Getting in flow : Time‐consuming trial‐and‐error investigations are required to diversify metal‐organic frameworks (MOFs) and predicting the synthesis conditions for such MOFs requires an understanding of the crystallization mechanism. The use of a microflow system, which efficiently captures non‐equilibrium states, led to the proposal of a three‐step nonclassical nucleation mechanism involving two kinds of intermediate.